SOME CONSEQUENCES FROM VEITSMAN’S THEOREM ON SPACES ANG FORCES FORMING THEM - Veitsman, E. V. (International Journal of Research -GRANTHAALAYAH, 2020)
Some consequences follow from Veitsman’s theorem. It is supposed that the physical time in space dependences on the state of the system under study. If space is in equilibrium, then there is no time known to us from physics in it. If the space is anisotropic then the time is to be a vector.